Pengaruh Tingkat Suku Bunga Terhadap Minat Nasabah Untuk Deposito Pada PT. Bank Perkreditan Rakyat Mitra Harmoni Mataram - Nasruddin; Murah (LPPM Universitas Gunung Rinjani, 2023)
The main problem in this study is whether there is influence from the interest rate component which consists of interest rate variables (X1), inflation rate variables (X2), LPS variables (X3), interbank competition variables (X4), and time period variable (X5) partially or simultaneously on customer interest in PT. BPR Mitra Harmoni Mataram. So the purpose of this study is to determine the effect of interest rates consisting of interest rates, inflation rates, LPS, competition between banks and time periods both simultaneously and partially on the interest of BPR Mitra Harmoni Mataram customers. This research is an associative research with the research method used is quantitative analysis. The number of sample in this study is 51 samples with a research questionnaire as a measurement instrument. From the research conducted, it is known that interest rates, which consist of interest rates, inflation rates, and LPS, have a positive and significant effect. This can be seen from the resulting regression equation, where Y = 0.319X1 + 0.569X2 + 0.376X3 – 0.157X4 – 0.087X5 – 0.259. Or in other words, if there is an increase in the amount of variable X, namely interest rates, inflation rates, and the Deposit Insurance Corporation, then satisfaction will increase and vice versa. So that in order to increase customer interest, it is also necessary to increase interest rates, inflation rates, and the Deposit Insurance Corporation. Keywords: Deposits, Customer Interest, Interest Rates. Abstrak Tujuan penelitian ini adalah untuk mengetahui pengaruh variabel suku bunga LPS (X1), tingkat inflasi (X2), LPS (X3), persaingan antar bank (X4), dan jangka waktu (X5) terhadap minat nasabah (Y) BPR Mitra Harmoni Mataram. Penelitian ini merupakan penelitian assosiatif dengan metode penelitian yang digunakan adalah analisis kuantitatif. Jumlah sampel penelitian ini sebanyak 51 sampel dengan kuesioner penelitian sebagai instrument pengukuran.Dari penelitian yang dilakukan diketahui bahwa tingkat suku bunga yang terdiri dari suku bunga, tingkat inflasi, dan LPS memberikan pengaruh yang positif dan signifikan. Hal ini dapat dilihat dari persamaan regresi yang dihasilkan, dimana Y= 0,319X1 + 0.569X2 + 0,376X3 – 0,157X4 – 0,087X5 – 0,259. Atau dengan kata lain jika terjadi penambahan jumlah pada variabel X yakni suku bunga, tingkat inflasi, dan LPS maka kepuasan akan meningkat dan begitu pula sebaliknya. Sehingga untuk dapat meningkatkan minat nasabah, maka perlu dilakukan peningkatan pula terhadap suku bunga, tingkat inflasi, dan LPS. Kata Kunci: Deposito, Minat Nasabah, Tingkat Suku Bunga.